INVESTIGATING EFL STUDENTS’ PERCEPTIONS OF APPLYING LEARNING MANAGEMENT SYSTEM IN LEARNING WRITING AT UNIVERSITY LEVEL - Siti Aliah (Journal of English Education Program (JEEP), 2020)
This study examines the student’s perceptions of applying a learning management system (LMS) in learning writing at the university level. This research aimed to examine the students’ perceptions about the usefulness of Canvas LMS in learning writing at the university level and to discover the students’ perceptions of applying Canvas LMS on their motivation in learning writing. The population of this research was the 32 students of English department Galuh University. The present study implemented a qualitative design in which a survey study and the data were collected through questionnaires and interviews. In analyzing the questionnaire the researcher used google form by displaying it into the figure and data interpretation based on the answer from a close-ended questionnaire, while the data from the interview was analyzed by displaying data interpretation from the interviewees. The result of the research showed the students had negative perceptions, in particular he troubles faced by the students. Some students felt not interested in applying Canvas LMS because it often had low motivation, trouble such as time, internet signal, system error, and so on. Keywords: Students’ perceptions, Canvas, LMS, Learning writing